(untitled) (Annals of Bangladesh Agriculture, 2026)
The cucurbit fruit fly Bactrocera cucurbitae (Coquillett) (Diptera: Tephritidae) is a key pest that causes substantial yield losses 30 100% depending on host species, season, and infestation pressure in ash gourd (also known as wax gourd; Benincasa hispida) (Thunb.) Cogn. production. This study evaluated the efficacy of integrating trap cropping (Local ash gourd germplasm “363”) along with chemical control (cypermethrin) compared with chemical control (cypermethrin) alone, trap cropping alone, and an untreated control in suppressing fruit fly populations and fruit infestations. A field experiment was conducted following a randomized complete block design with four treatments during the period of 90 days. Fruit fly populations and infestation levels were monitored at 45, 60, 75, and 90 days after treatment. The results demonstrated that the combination of trap cropping and chemical insecticide application significantly reduced fruit fly density (2.25 fruit fly/plot) and fruit damage (0.875 infested fruits/plot) compared to the other treatments, while the highest fruit fly density (14.2 fruit fly/plot) and fruit damage (3.75 infested fruits/plot) were recorded in the untreated control. Chemical control alone provided moderate suppression, whereas trap cropping alone showed limited effectiveness. The untreated control sustained the highest pest populations and fruit infestations. Ann. Bangladesh Agric. 29(2): 141-155